Estimate of Condition Number for Some Discrete Ill-Posed Equations (Journal of Computational Mathematics, 1991)
This paper extends the numerical method and the estimate of the condition number for some discrete ill-posed equations with positive definite matrix in [2] to the case with generalized positive definite matrix.